The biomechanical determinants of increased speed in passively assisted human-powered locomotion - Minetti, A. E. (The Journal of Physiology, 2002)
The endeavour for exploration and the innate curiosity pushed humans to adapt locomotion to different environments, despite the inherent limits in body anatomy and physiology. This process, confined today to leisure because of the availability of active machines, started a couple of millennia ago and benefited from passive locomotor tools. The tools can be grouped into terrestrial, aquatic and aerial categories, with the common feature of enhancing muscle performance to achieve a higher mechanical power, economy, sustainable speed and/or distance range. The first tools devoted to increase the human performance in the standing long jump were HALTERES, hand-held loads (1.2Ð4.5 kg) introduced in ancient Olympics pentathlon events (500-300 BC). Their role was: (a) to produce a higher ground reaction force by a more efficient use of shoulder extensor muscles, and (b) to alter the position of the body centre of mass (BCOM) at take-off (more anterior) and landing (more posterior). There are clues (Minetti, 2002) that these effects increased the jump range. While studying the ability of our musculo-skeletal system to store and return elastic energy, Tom McMahon (1979) designed a purposely 'TUNED' TRACK where the surface stiffness was controlled and athletes were able to run faster. However, running speed is limited by the constraint imposed by foot contact with the ground, which forces the lower limbs to be moved, with respect to BCOM, at the same speed the BCOM moves with respect to the environment. At that (increasing) speed, muscles operate (both for relocation and pushing) in a disadvantageous range of the force/velocity diagram. The invention of skating, in all its forms, partially solves this problem by allowing the appendages to move and push at a slower, more efficient, speed. ICE/IN-LINE SKATING (3000 BCÐca 1980), also used for transportation on the iced Amsterdam canals (about 14th century), is in its modern form the fastest non-wheeled human-powered locomotion (very low friction: 0.003Ð0.007). The lateral push while sliding allows knee and ankle extensor muscles to operate within the optimal contraction speed range. The reduced added mass and speed of limbs with respect to BCOM also implies a low mechanical internal work (WINT, i.e. the work necessary to accelerate body segment with respect to BCOM). The modern roller in-line skating, while being slower because of the higher rolling resistance, benefits from the same physiomechanical strategy of ice skating. Another success of the skating protocol can be found in CROSS-COUNTRY SKI (2000 BCÐ1980). Originally a means of travel and communication in Scandinavia and Russia, it is today the second fastest non-wheeled locomotion because of the very low friction (0.05Ð0.20) and the small added mass involved. Skating is the fastest technique, which adopted the ice-skating strategy for lower limbs (lowering WINT and increasing muscle efficiency) and made a better use of 'energy recovery', i.e. the exchange between the potential and kinetic energy of BCOM (Cavagna et al. 1976), and the related mechanical external work (WEXT, Minetti et al. 2001a). The other available techniques, namely the diagonal stride and the double pole, are slower mainly because the propulsion is achieved by the push on the snow of skis and poles, which stop with respect to the ground, with the above explained detrimental effects on WINT and the muscle efficiency. A great advancement in terrestrial human-powered locomotion has been achieved when the wheel helped to sustain the BCOM, thus avoiding spending metabolic energy to counteract gravity, both isometrically and during the typical vertical oscillations as occurring in walking/running/skating. The idea behind the BICYCLE (1820Ð) was an alteration of body geometry in order to escape from the rimless wheel metaphor of legged locomotion. By preventing the vertical displacements of BCOM, the lower limb muscles can be used mainly to overcome rolling resistance and air drag. By progressing from the Hobby Horse (1820), where the rider pushed directly on the ground, to the High Wheeler (1870) and the modern bicycle (1890), the metabolically equivalent cruising speed, with respect to walking (1.5 m s-1), increased 3.3 times (~5.0 m s-1, Minetti et al. 2001b). The major determinants of locomotor economy improvement in cycling evolution were: (1) the decrease of the overall bicycle mass (from 24 to 16 kg), which helped to further decrease (2) the decreased rolling resistance (0.027 to 0.008), due to the transition from metal to solid and inflatable tyres, (3) the concurrent lengthening of the distance travelled per pedal revolution (2.8 to 5.5 m), which caused (4) the decrease of pedalling rate (fr) at a given speed and, consequently, (5) the decrease of WINT (which in cycling depends on fr3). In addition, the last two effects maximized the efficiency of knee extensor muscles at high progression speed, allowing them to keep on contracting within the optimal speed range. The modern racing bicycle is the fastest human-powered vehicle available. Aquatic locomotion benefited by appendages for hands and feet devoted to improve propulsion. With respect to normal kick swimming FIN SWIMMING (fin pairs 1680Ð1935, monofin 1967) decreases the metabolic cost by about 40 %, allowing 0.2 m s-1 speed increase. It has been found that WINT and the kinetic energy imparted to the amount of water not involved in propulsion decrease by using fins, thus the Froude efficiency and the hydraulic efficiency increase, respectively (Zamparo et al. 2002). In conclusion, the increase of economy/cruising speed (or of jumping range) has been obtained by each of the illustrated passive appendices throughout a combination of the following strategies: (a) the decrease of WEXT, (b) the decrease of WINT, (c) the modification of body configuration, devoted to retain muscle performance optimization.